Analysis of Student Satisfaction Levels Toward Computer Laboratory Facilities at STMIK Widya Cipta Dharma Using the Importance Performance Analysis Method - Nabila Marsya Zikryanti Raharjo; Ita Arfyanti; Yunita Yunita (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
The computer laboratory is one of the important facilities in supporting practical activities and technology-based learning at STMIK Widya Cipta Dharma. This study aims to analyze the level of student satisfaction with the computer laboratory facilities and to determine improvement priorities that need to be addressed. The method used in this study is Importance Performance Analysis (IPA), which measures the relationship between the level of importance and the performance level of each laboratory service attribute. Data were collected through questionnaires distributed to 129 students who use the laboratory. The results show that, in general, students are satisfied with the laboratory facilities, especially in terms of room comfort, practicum module suitability, and software availability. The overall satisfaction level reached 93%, indicating that most facilities have met student expectations. However, several attributes require greater attention, such as internet connection speed, hardware condition, and peripheral functionality including monitors, keyboards, and mice. Based on the IPA Cartesian diagram analysis, these attributes are located in the main priority quadrant for improvement because they are considered highly important but their performance is still below expectations. Meanwhile, attributes related to assistant responsiveness and module clarity were included in the maintain performance quadrant. The findings of this study are expected to provide useful input for laboratory management in improving service quality and optimizing facilities to better support student learning activities.